Electronic cigarette advertising and teen smoking initiation. (April 2020) - Hansen, Julia; Hanewinkel, Reiner; Morgenstern, Matthis
Highlights: Study examined the impact of e-cig marketing on smoking behavior. Exposure to e-cig advertisements increased the likelihood of future e-cigarette use. Exposure to e-cig marketing was associated with the use of conventional cigarettes. Abstract: Introduction: The objective of this study was to investigate the associations between recall of exposure to e-cigarette advertisements and initial use of e-cigarettes, conventional cigarettes and hookahs one year later among German adolescents. Methods: Longitudinal school-based survey with a sample of 4, 529 German adolescents (mean age = 12.5 years, SD = 1.55). Baseline assessment took place in the fall/winter 2016/2017, and a follow-up assessment 12 months later. Exposure to e-cigarette advertisements was measured at baseline with self-rated contact frequency to three advertising images. Multilevel mixed-effect logistic regression models were used to assess associations between exposure to e-cigarette advertisements at baseline and adolescents' initiation of e-cigarette, smoking and hookah use one year later. Results: About 14% (N = 472) baseline never-users initiated e-cigarette use within one year, about 11% (N = 384) initiated cigarette use, and 12% (N = 406) used a hookah for the first time within the observation period. After statistical control for age, gender, school type, subjective socioeconomic status, sensation seeking, lifetime smoking behavior and peer substance use, adolescents with higher contact to e-cigarette advertisements had higher proportion of subsequent e-cigarette (aOR = 1.37 (CI = 1.04–1.81) p = .024), cigarette (aOR = 1.44 (CI = 1.09–1.91) p = .010), and hookah use (aOR = 1.82 (CI = 1.37–2.42) p < .001). Conclusions: This longitudinal study demonstrates that exposure to e-cigarette advertisements may increase the likelihood of initial use of e-cigarettes, cigarettes, and hookahs. Findings raise concerns about e-cigarette marketing regulations in Germany, and about the broader impact of e-cigarette advertising on traditional smoking.